Identifying and managing refractory migraine: barriers and opportunities? - Linda D’Antona (The Journal of Headache and Pain, 2019)
Abstract The term refractory migraine has been used to describe persistent headache that is difficult to treat or fails to respond to standard and/or aggressive treatments. This subgroup of migraine patients are generally highly disabled and experience impaired quality of life, despite optimal treatments. Several definitions and criteria for refractory migraine have been published, but as yet, an accepted or established definition is not available. This article reviews the published criteria and proposes a new set of criteria. The epidemiology, pathophysiology and management options are also reviewed.